Menggali Potensi Kewirausahaan : Strategi, Tantangan, dan Peluang di Era Digital - Melkisedek Melkisedek; Tia Neonane; Yosia Belo (Pusat Riset dan Inovasi Nasional, 2025)
Entrepreneurship plays a vital role in global economic progress and is the main path to financial independence and innovation. Amidst the rapid development of technology and rapid changes, new opportunities for entrepreneurs are wide open, but they also have to face various challenges that require wise management. This article reviews five important aspects for entrepreneurs in the digital era. First, the importance of recognizing business opportunities that arise from technological advances and digital market transformation. Second, the implementation of sustainable innovation strategies to remain competitive in the market. Third, managing risks and uncertainties in the digital business world. Fourth, utilizing technology to improve business operational efficiency. Fifth, the importance of creating a strong brand and building customer loyalty in a competitive market. By understanding and implementing these five aspects, entrepreneurs can maximize their potential and achieve sustainable success in the ever-evolving business world.